Clinical Holistic Medicine: Holistic Treatment of Rape and Incest Trauma - Søren Ventegodt; Isack Kandel; Shimshon Neikrug; Joav Merric (The Scientific World Journal)
Studies indicate that at least 15% of the female population in western countries has experienced sexual abuse and severe sexual traumas. This paper explains how even serious sexual abuse and trauma can be healed when care and resources encourage the patient to return to the painful life events. When the physician cares and receives the trust of the patient, emotional holding and processing will follow quite naturally. Spontaneous regression seems to be an almost pain-free way of integrating the severe traumas from earlier experiences of rape and incest. This technique is a recommended alternative to classical timeline therapy using therapeutic commands. When traumatized patients distance themselves from their soul (feelings, sexuality, and existential depth), they often lose their energy and enjoyment of life. However, this does not mean that they are lost to life. Although it may seem paradoxical, a severe trauma may be a unique opportunity to regain enjoyment of life. The patient will often be richly rewarded for the extensive work of clearing and sorting out in order to experience a new depth in his or her existence and emotional life, with a new ability to understand life in general and other people in particular. So what may look like a tragedy can be transformed into a unique gift; if the patient gets sufficient support, there is the possibility of healing and learning. Consciousness-based medicine seems to provide severely traumatized patients with the quality of support and care needed for their soul to heal.